ANALISIS IMPLEMENTASI ELECTRONIC COMMERCE UNTUK MENINGKATKAN OMSET PENJUALAN BUTIK MERY BERBASIS WEB MOBILE - Mery Efriyanti; Garaika Garaika; Rita Irviani (Jurnal Signaling, 2018)
Mery Boutique is a place that provides a variety of women's and men's batik products that focus on service and good product quality. The purpose of doing this research is for an information system for selling batik products for women and men based on mobile web. This research is to develop an online-based sales information system in Meri boutique, the methodology used for the development of e-commerce systems is a structured methodology with a waterfall model. The results of this research are the application of e-commerce applications can help meri boutique businesses to develop more and increase sales turnover so that it can have implications for improving service to customers, consumers and administrative management.